Agents Of Change : The Problematic Landscape of Pakistan's k-12 Education and the People Leading the Change - Amjad Noorani and Nadeem Hussain; Foreword by Buluswar, Shashi (Karachi Oxford University Press, 2021)
Agents of Change is a compilation of thought-provoking insights, opinions, personal stories, and suggested actions for change in the K-12 education system in Pakistan.
Include Index
Keywords: Education -- Social, Political and Economic Imperatives of Education -- Fixing the Problematic Education